2011
DOI: 10.1103/physrevlett.106.015701
|View full text |Cite
|
Sign up to set email alerts
|

Glass Transition of the Monodisperse Gaussian Core Model

Abstract: We numerically investigate the dynamical properties of the one-component Gaussian core model in supercooled states. We find that nucleation is increasingly suppressed with increasing density. The system concomitantly exhibits glassy, slow dynamics characterized by the two-step stretched exponential relaxation of the density correlation and a drastic increase of the relaxation time. We also find a weaker violation of the Stokes-Einstein relation and a smaller non-Gaussian parameter than in typical model glass f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(32 citation statements)
references
References 33 publications
0
32
0
Order By: Relevance
“…F. Gaussian core model The Gaussian core model (GCM) [53,54], which is not strongly correlating, is defined by a Gaussian pair potential and thus has a finite potential energy at zero separation. The high-density regime of the GCM model (ρ > 1.5) has recently received attention as a singlecomponent model glass former [55] because it is not prone to crystallization and shows the characteristic features of glass-forming liquids (large viscosity, two-step relaxation, etc). Figure 15 shows the RDF and ISF for the GCM liquid.…”
Section: E Lennard-jones Gaussian Liquidmentioning
confidence: 99%
“…F. Gaussian core model The Gaussian core model (GCM) [53,54], which is not strongly correlating, is defined by a Gaussian pair potential and thus has a finite potential energy at zero separation. The high-density regime of the GCM model (ρ > 1.5) has recently received attention as a singlecomponent model glass former [55] because it is not prone to crystallization and shows the characteristic features of glass-forming liquids (large viscosity, two-step relaxation, etc). Figure 15 shows the RDF and ISF for the GCM liquid.…”
Section: E Lennard-jones Gaussian Liquidmentioning
confidence: 99%
“…Therefore, especially in theoretical work, the SE relation is often written in terms of the α-relaxation time, τ α , instead of the viscosity. [11][12][13][14] The SE relation was derived for a mesoscopic ball suspended in a continuum fluid; however, many experiments have demonstrated that in many liquids, Eq. (1) holds at a microscopic level over a large temperature range for the self-diffusion coefficient.…”
Section: Introductionmentioning
confidence: 99%
“…21,22 In the past several decades, the SE relation, especially its breakdown, has attracted considerable research interest of scientists in many fields. [7][8][9][10][11][12][13][14][15][16][17][23][24][25][26][27][28][29] There are three unsolved, open questions regarding the breakdown of SE relation, namely, how far can one cool down the liquid before the SE relation breaks down, what mechanism is responsible for the breakdown, and how does one predict the onset of the breakdown quantitatively. The answers to these three interrelated questions are still discussed controversially.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has recently been shown that generalized Langevin theories 24,33,34 can qualitatively (but not yet quantitatively) predict the anomalous density dependence of the long-time self-diffusivity observed in Brownian dynamics simulations of the Gaussian-core model. Likewise, mode-coupling theory has been able to capture some of the nonmonotonic dynamic trends displayed by fluids of particles that interact via starpolymer-like, 23 harmonic, 35 Hertzian, 29 or Gaussian-core 27,36 pair potentials. Kinetic theory has also been used to gain insights into the nontrivial temperature-and density-dependent a) Author to whom correspondence should be addressed.…”
mentioning
confidence: 99%